2014
DOI: 10.1186/1471-2474-15-40
|View full text |Cite
|
Sign up to set email alerts
|

Posterior short segment pedicle screw fixation and TLIF for the treatment of unstable thoracolumbar/lumbar fracture

Abstract: BackgroundCurrently, Posterior Short Segment Pedicle Screw Fixation is a popular procedure for treating unstable thoracolumbar/lumbar burst fracture. But progressive kyphosis and a high rate of hardware failure because of lack of the anterior column support remains a concern. The efficacy of different methods remains debatable and each technique has its advantages and disadvantages.MethodsA consecutive series of 20 patients with isolated thoracolumbar/lumbar burst fractures were treated by posterior short segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…Their mean age was 33.12 ± 8.57 years (range 20 -60 years). Wang et al .studied on 20 patients with traumatic fracture of the thoracolumbar spine underwent spinal surgery and found that their mean age was 38.4 years (range 17 -66 years) which was similar to this study [17]. It was reported that thoracolumbar spine fractures were one of the most common fractures in the young healthy population [3] [17].…”
Section: Discussionsupporting
confidence: 85%
“…Their mean age was 33.12 ± 8.57 years (range 20 -60 years). Wang et al .studied on 20 patients with traumatic fracture of the thoracolumbar spine underwent spinal surgery and found that their mean age was 38.4 years (range 17 -66 years) which was similar to this study [17]. It was reported that thoracolumbar spine fractures were one of the most common fractures in the young healthy population [3] [17].…”
Section: Discussionsupporting
confidence: 85%
“…And it is associated with shorter operating time, less blood loss, shorter hospital stay, and lower incidence of complications [6][7][8][9][10][11] . In recent years, TLIF also received a good clinical application in treatment of degenerative lumbar scoliosis, recurrent lumbar disc herniation, thoracolumbar fracture or degenerative diseases, and so on [12][13][14][15][16] . And with the continuous development of minimally invasive operating techniques, minimally invasive TLIF gained wide clinical popularity, even became a same-day discharge or outpatient operation 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various controversies associated with management of unstable fractures of the thoracolumbar region, whether to use posterior or anterior approach; posterior approach is one of the common approaches to the fracture management. 9 There are apprehensions regarding the high rate of hardware failure due to lack of anterior support and progressive kyphosis. [10][11][12][13][14][15] Inspite of the mentioned complications, the clinical prognosis is satisfactory.…”
Section: Discussionmentioning
confidence: 99%